Traffic noise in crossings and roundabouts - Bredenfeldt, Henrik; Nilsson, Andreas (My University, 2004)
The aim of this project has been to measure the equivalent continuous sound pressure level, Leq, close to crossings and roundabouts. The measurement results have been compared with calculations according to the Nord 2000 method. The main aim can be divided into three parts: - To come up with a method on how to measure traffic noise close to crossings and roundabouts and how to compare the measurements with the calculation model - To find out if there is a significant difference between the calculation model and reality - If there is,what is this difference due to and how does it look. The equivalent continuous sound pressure level, Leq, has been measured in 1/3-octave bands at three crossings and three roundabouts in the city Borås, Sweden. Measurements have been performed on the traffic passing through these crossings/roundabouts. Three different vehicle categories have been used: cars, dual-axle heavy vehicles and milti-axle heavy vehicles. Four microphones have been placed along the connecting roads at the approximate distances 10, 43, 76 and 109 m, counted from the crossing/roundabout. The perpendicular distance from the microphone to the road varies due to the existing terrain, but the height of the microphone positions were always set to 3 m above the local ground. In most cases passenger cars dominated the traffic. The measurements have been compared with the calculation model Nord 2000 and the difference has been analysed. The results indicate that the measured A-weighted Leq close to crossings and roundabouts is lower than the calculated value if the speed limit is used as input in the calculation model. This is probably due to the fact that the speed in the crossing/roundabout is lower than the speed limit which was 50 km/h. When observing the difference between a position close to the crossing/roundabout and a position at a distance that is not affected by the crossing/roundabout, i.e. the traffic is free flowing; all results indicate that the A-weighted Leq is lower in the position close to the crossing/roundabout. This should be due to the fact that the speed is lower close to the crossings than at the position with free flowing traffic.
Keywords: Samhällsbyggnadsteknik; Civil Engineering